Janice VanCleave's geography for every kid easy activities that make learning geography fun - VanCleave, Janice (Wiley, 1993)
SUMMARY: Introduces basic concepts of geography through simple problems and activities such as constructing a clay map, making a compass rose, and plotting the track of a hurricane.